2011
DOI: 10.1016/j.neuroscience.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and redox proteomics analyses of an Alzheimer disease transgenic mouse model: effects of the amyloid-β peptide of amyloid precursor proteinΞ

Abstract: Among the pathological factors known to be associated with Alzheimer disease (AD), oxidative stress induced by the amyloid-β peptide (Aβ) has been demonstrated to play a key role in human brain and animal models of AD. Recently, we reported elevated levels of oxidative damage in the brain of a transgenic (Tg) AD mouse model with Swedish and Indiana familial AD mutations in human amyloid precursor protein (APP) [PDAPP mice, line J20], as evidenced by increased levels of protein carbonyls, 3-nitrotyrosine, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 82 publications
4
44
0
Order By: Relevance
“…The increase in the levels of mitochondrial-related proteins such as ATP synthase subunit a, VATB2, and VDAC1 could indicate that their levels are decreased in J20 Tg mice due to the presence of Met in Ab, while M631L Tg mice are unaffected. In our previous studies conducted on the proteome changes in J20 Tg mice, we observed increased expression levels of glycolytic and mitochondrial proteins (6). VATB2 also plays a role in autophagy, which is consistent with the suggestion that in the absence of oxidative stress due to the absence of Met-35 in Ab(1-42) of APP, autophagic processes work well, but are compromised in J20 mice.…”
Section: Importance Of Ab-resident Methionine In Ad Pathogenesissupporting
confidence: 90%
See 3 more Smart Citations
“…The increase in the levels of mitochondrial-related proteins such as ATP synthase subunit a, VATB2, and VDAC1 could indicate that their levels are decreased in J20 Tg mice due to the presence of Met in Ab, while M631L Tg mice are unaffected. In our previous studies conducted on the proteome changes in J20 Tg mice, we observed increased expression levels of glycolytic and mitochondrial proteins (6). VATB2 also plays a role in autophagy, which is consistent with the suggestion that in the absence of oxidative stress due to the absence of Met-35 in Ab(1-42) of APP, autophagic processes work well, but are compromised in J20 mice.…”
Section: Importance Of Ab-resident Methionine In Ad Pathogenesissupporting
confidence: 90%
“…In the current study, we observed decreased levels of Pin-1 in M631L Tg mice relative to J20 Tg mice. In the comparison between J20 Tg mice relative to J20 NTg animals, we previously observed an increase in Pin-1 expression, which may indicate the brain's attempt to reduce elevated Ab levels and prevent oligomeric Ab formation (6).…”
Section: Alterations In Structure and Neuronal Transmissionmentioning
confidence: 87%
See 2 more Smart Citations
“…Redox proteomic analysis of the post-mortem brains of AD patients revealed the presence of oxidative modifications of various protein substrates. Among them, some are relevant mitochondrial proteins, such as ATP synthase -and -chain and VDAC (Robinson et al, 2011). These mitochondrial r e s i d e n t p r o t e i n s w e r e f o u n d t o b e o x i d ised in the hippocampus and the observed modifications could play a role in the mitochondrial dysfunction and cell death observed in AD.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%